2019
DOI: 10.3390/molecules24234219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forsythiaside A on the RLRs Signaling Pathway in the Lungs of Mice Infected with the Influenza A Virus FM1 Strain

Abstract: Forsythiaside A, a phenylethanoid glycoside monomer extracted from Forsythia suspensa, shows anti-inflammatory, anti-infective, anti-oxidative, and antiviral pharmacological effects. The precise mechanism underlying the antiviral action of forsythiaside A is not completely clear. Therefore, in this study, we aimed to determine whether the anti-influenza action of forsythiaside A occurs via the retinoic acid-inducible gene-I–like receptors (RLRs) signaling pathway in the lung immune cells. Forsythiaside A was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Protein expression of p-p65 was upregulated in H2O2-stimulated H9c2 cells suggesting that the NF-κB pathway was activated. Forsythiaside A was shown to decrease NF-κB expression to alleviate virusinduced lung tissue damage [15]. In this study, forsythiaside A reduced p-p65 expression in H2O2-induced H9c2 cells.…”
Section: Discussionmentioning
confidence: 48%
“…Protein expression of p-p65 was upregulated in H2O2-stimulated H9c2 cells suggesting that the NF-κB pathway was activated. Forsythiaside A was shown to decrease NF-κB expression to alleviate virusinduced lung tissue damage [15]. In this study, forsythiaside A reduced p-p65 expression in H2O2-induced H9c2 cells.…”
Section: Discussionmentioning
confidence: 48%
“…The aqueous extract of the fruit of Forsythia is widely used in traditional medicines against many frequently occurring disorders including inflammation, pain, fever, nausea, vomiting and abscess, leading to a rich treasure of information on its use ( Wang et al, 2018 ). Forsythoside A ( Law et al, 2017 ; Zheng et al, 2019 ) and labdane diterpenoids ( Xiang et al, 2020 ; Zhao et al, 2020 ) isolated from the fruits of Forsythia suspensa showed antiviral activities and, as already stated in the Introduction, Forsythia is one of the herbal medicines, which were successfully used for the therapy of the SARS-CoV infected patients in the 2002/2003 SARS epidemic ( Liu et al, 2006 ; 2012a , 2012b ; Wang et al, 2014 ; Luo et al, 2020 ).…”
Section: Forsythia Suspensa (Fructus Forsythiae)mentioning
confidence: 66%
“…The number of neutrophils as mediators of inflammation and macrophages was reduced which typically reduced inflammations in the lungs of cigarette and smoke-induced mice [ 154 ]. It was reported to act as an immunomodulatory agent which showed an increment in anti-inflammatory cytokines after treatment and restrained the activation of T cell immune response [ 172 ]. Forsythiaside A could be developed as a possible therapeutic candidate against respiratory complications.…”
Section: Some Promising Natural Products and Their Pharmacologymentioning
confidence: 99%